ТО THE QUESTION OF PRACTICALPRÉPARATION OFFUTURE TEACHERS OF FINE ART ON THE ARTISTICALLY-GRAPHIC FACULTIES OF PEDAGOGICAL ESTABLISHMENTS OF ÉDUCATION - T.P. Kovalchuk (Academy of Cognitive and Natural Sciences, 2022)
The questions of practicity prepared of the art-graphie faculty students for art décorative and artistic endeavour.